RADIATION PREPARATION OF SMART HYDROGEL HAS ANTIMICROBIAL PROPERTIES FOR CONTROLLED RELEASE OF CIPROFLOXACIN IN DRUG DELIVERY SYSTEMS - Maziad, Nabila Ahmed; El-hamouly, Sabrnal; Zied, Ebrhem; A El Kelani, Tamer; Rabie Nasef, Nada (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The objective of the present work was to synthesize copolymer hydrogel composed of poly acrylic acid (PAAc) and PAAc/pectin, which are very sensitive to environmental stimulus, this feature is important for their application in biomedical applications, due to its unique properties, which can resemble human living organs, wound dressing, drug delivery systems. Gamma radiation induces synthesis and modification of monomer to polymer hydrogel was studied. The effect of different parameter onto preparation of smart hydrogel such as monomer concentration, radiation dose on to swelling percent of the prepared copolymer hydrogel have been studied, gel fraction have been studied as a function of swelling ratio. Structure characterization of the prepared copolymer hydrogel have been investigated using Fourier transform infrared spectroscopy, The morphological structure using X-ray diffraction analysis and scanning electron microscopy have been studied. The swelling properties of the prepared copolymers have been studied at different time and pH. It was found that the swelling percent increases as the time increase and increases as pH increase and the maximum swelling occurs at pH 6 with the value of 19,000% for PAAc hydrogel and 10,000% for PAAc/pectin hydrogels after 24 hrs. Drug loading measurements using ciprofloxacin (CPFX) drug at pH 7 for PAAc hydrogel after 24 hrs and at pH 11 for PAAc/pectin hydrogels. Studies of drugreleasing of CPFX as drug model have been investigated, at different time and pH and it was found that the drug release incases as pH increase and the maximum release occurs at pH 4 for PAAc and pH (3,8) for PAAc/pectin hydrogels, the antimicrobial activity of the synthesized copolymeric hydrogel under study was evaluated based on the diameters of clear zone surrounding the polymeric substance (disk diffusion test) this proved that polymeric hydrogel can be used as antibacterial agent. Keywords: Radiation, Copolymerization, Pectin, Acrylic monomers, Drug release.